Kindergarten Teachers Training in Integrating Anti-Corruption Education through Storytelling and Game - Grace Kartika Ratih; Ade Iriani; Yari Dwikurnaningsih (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
There are many ways to prevent corruption, one of them is in education. This study aims to provide training to kindergarten teachers on how to integrate anti-corruption values into teaching and learning activities using storytelling and game methods. This research applied mix method and took the setting in 2 schools in Salatiga, Indonesia. The qualitative data from the interviews were processed by transcribing the answers to the research questions, then sorting out the answers. The pre-test and post-test quantitative data were processed using Wilcoxon technique in SPSS.  From the test it is known Asymp.Sig (2-tailed) is 0.011. Because the value of 0.011 is smaller than 0.05, it can be concluded that the hypothesis is accepted. This means that there is an increase in competence about Anti-Corruption Education before and after training using the module. This research also contributes to expanding literacy source for kindergarten teachers in the form of anti-corruption education training modules